Hemoglobin Mass, Blood Volume and VO2max of Trained and Untrained Children and Adolescents Living at Different Altitudes - Mancera-Soto, Erica Mabel; Ramos-Caballero, Diana Marcela; Rojas J., Joel A.; Duque, Lohover; Chaves-Gomez, Sandra; Cristancho-Mejía, Edgar; Schmidt, Walter Franz-Joachim (Frontiers in Physiology, 2022)
Introduction: To a considerable extent, the magnitude of blood volume (BV) and hemoglobin mass (Hbmass) contribute to the maximum O2-uptake (VO2max), especially in endurance-trained athletes. However, the development of Hbmass and BV and their relationships with VO2max during childhood are unknown. The aim of the present cross-sectional study was to investigate Hbmass and BV and their relationships with VO2max in children and adolescents. In addition, the possible influence of endurance training and chronic hypoxia was evaluated. Methods: A total of 475 differently trained children and adolescents (girls n=217, boys n=258; untrained n=171, endurance trained n=304) living at two different altitudes ( 1000 m, n=204, 2600 m, n=271) and 9 to 18 years old participated in the study. The stage of puberty was determined according to Tanner; Hbmass and blood volumes were determined by CO rebreathing; and VO2max was determined by cycle ergometry and for runners on the treadmill. Results: Before puberty, there was no association between training status and Hbmass or BV. During and after puberty, we found 7% to 10% higher values in the trained groups. Living at a moderate altitude had a uniformly positive effect of approx. 7% on Hbmass in all groups and no effect on BV. The VO2max before, during and after puberty was strongly associated with training (pre-pubertyprepuberty: boys +27%, girls +26%; mid-puberty: +42% and +45%; end-postpuberty: +43% and +47%) but not with altitude. The associated effects of training in the pre-pubertalprepubertal groups were independent of Hbmass and BV, while in the mid- and post-pubertalpostpubertal groups, 25% of the training effect could be attributed to the elevated Hbmass. Conclusions: The associated effects of training on Hbmass and blood volume, resulting in increased VO2max, can only be observed after the onset of puberty.